Konflik Sosial Bernuansa Sosio-Emosi serta Penyelesaiannya dalam Persepktif BK Pribadi-Sosial - Tri Diyah Lestari; Isbandiyah Isbandiyah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of the study was to identify social conflicts with socio-emotional nuances and to resolve them in the personal-sosial counseling perspective that occurred in the people of Bumisari Natar Village, Lampung. The research method uses descriptive qualitative methods. There are 6 people as sources of research data who are considered to have sufficient knowledge about the problems in this study. Collecting data with the method of observation, interviews, and documentation. Analysis of the data using the interactive analysis of the Milles and Hubarman model which consists of steps of data reduction, data presentation, and drawing conclusions. The results showed that the solution to sosial conflict resolution could be done through personal sosial guidance with the help of village officials and sosial workers. It begins with the planning, implementation, evaluation and follow-up stages, both individually and in groups. Conclusion The research shows that the cause of sosial conflict is the existence of non-realistic conflict factors such as feelings of envy, irritability, the presence of a third party who pits each other, incitement, backbiting, envy, unruly, and sosial jealousy. Keywords: Social Conflict, Social Interaction, Society